2013
DOI: 10.1021/jp403065y
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electrochemical Quartz Crystal Admittance Methodology for Tracking Compositional and Mechanical Changes in Porous Carbon Electrodes

Abstract: The state-of-the-art in supercapacitors and capacitive deionization technology utilizes high surface area carbons which store energy in electric double layers (EDLs) at the carbon surface/electrolyte solution interface. To reach high energy density, a fundamental understanding of the nature of ion and solvent adsorption into their porous volume is required. We review herein a novel approach to in situ gravimetric monitoring of the compositional changes in porous carbon electrodes during their charging using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 41 publications
6
108
0
Order By: Relevance
“…2C) The participation of the anions (Cl -) to the electroadsorption process was also detected at around the PZC (Fig. 2C,D) probably due to the permselectivity failure of the SWCNT films around this value leading to the mixed adsorption [7]. Their transfer resistance is high around PZC which decreases at more anodic potentials i.e.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…2C) The participation of the anions (Cl -) to the electroadsorption process was also detected at around the PZC (Fig. 2C,D) probably due to the permselectivity failure of the SWCNT films around this value leading to the mixed adsorption [7]. Their transfer resistance is high around PZC which decreases at more anodic potentials i.e.…”
Section: Resultsmentioning
confidence: 87%
“…Answering the questions concerning the charging mechanisms is experimentally difficult because there are not any appropriate electrochemical or physicochemical methods that allow a direct access to such information. Recent electrochemical quartz crystal microbalance (EQCM) based analyses started to address these questions [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…calculated for the experiment related to Figure 3 was 9.39. Based on parallel studies of complex electrochemical processes by EQCM, [21][22][23] we can attribute such a discrepancy to viscoelastic effects that limit the simple applicability of the Sauerbrey equation 24 for these measurements. All our tests with MgTFSI 2 /MgCl 2 solutions showed that during prolonged electrochemical measurements, an un-identified by-product was formed (and at least part of it precipitated on the electrode surface), a by-product which is associated with the passage of faradaic currents.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported that the viscoelastic properties of the electroactive polymer play a crucial role in the electrogravimetric response if the film is not sufficiently thin or rigid [45]. More importantly, the viscoelastic change with electrochemical cycling is supposed to have a great influence on the electrochemical performance of the film primarily because volumetric changes during the redox process (insertion or expulsion of charged and non-charged species) are strongly associated with the viscoelastic properties of the polymer chains.…”
Section: Viscoelastic Property Changes Upon Film Agingmentioning
confidence: 99%